Fundamentals of financial accounting - Tracy, John A. (Santa Barbra, New York John Wiley, 1978)
This textbook is designed for an introductory financial accounting course. It provides a solid foundation for those students going to intermediate financial accounting course sequence
Includes index.
ucj 07/11/2018
Loans
Keywords: Accounting